2007
DOI: 10.1016/j.marenvres.2007.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Copper complexation by fulvic acid affects copper toxicity to the larvae of the polychaete Hydroides elegans

Abstract: Copper toxicity is influenced by a variety of environmental factors including dissolved organic matter (DOM). We examined the complexation of copper by fulvic acid (FA), one of the major components of DOM, by measuring the decline in labile copper by anodic stripping voltammetrically (ASV). The data were described using a one-site ligand binding model, with a ligand concentration of 0.19micromol site mg(-1) C, and a logK' of 6.2. The model was used to predict labile copper concentration in a bioassay designed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…In addition, the authors reported that the binding between Cu and fulvic acid was weaker than that between Cu and humic acid. However, the lowest DOM concentration used (8 mg C/L) was considerably higher than the environmentally relevant salt water DOM concentrations tested in the present study, that is, 0.5 mg C/L (SBAT‐DOM) or 2.2 mg C/L (NBAT‐DOM). Therefore, it is possible that these DOM concentrations were not high enough to show a protective effect against the acute Cu toxicity in seawater (salinity 30 ppt).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the authors reported that the binding between Cu and fulvic acid was weaker than that between Cu and humic acid. However, the lowest DOM concentration used (8 mg C/L) was considerably higher than the environmentally relevant salt water DOM concentrations tested in the present study, that is, 0.5 mg C/L (SBAT‐DOM) or 2.2 mg C/L (NBAT‐DOM). Therefore, it is possible that these DOM concentrations were not high enough to show a protective effect against the acute Cu toxicity in seawater (salinity 30 ppt).…”
Section: Discussionmentioning
confidence: 99%
“…(Qiu et al 2007;Xie et al 2005). The results showed that settlement of competent larvae of this species was not affected by relatively short periods (1-2 days) of exposure to high concentrations of Cu (300 mg l 71 ), but with a longer exposure period (3 days) larval settlement was significantly decreased at 100 mg l 71 .…”
Section: Biofilmsmentioning
confidence: 87%
“…High concentrations of Cu have led to concern over their harmful impact on the marine environment. Cu stress in many marine invertebrates such as corals (Smith et al 2003), polychaetes (Xie et al 2005;Qiu et al 2007), mussels (Hoare et al 1995), barnacles , sea urchins (Ferna´ndez and Beiras 2001), and ascidians (Bellas et al 2004) has been demonstrated by ecotoxicity bioassays, which are mainly focused on embryos, larvae, juveniles, or adults. The effects of Cu stress on larval settlement, which is the most critical stage in life cycles linking pelagic and sessile life (Pawlik 1992), however, remain largely unexplored.…”
Section: Copper Affects Biofilm Inductiveness To Larval Settlement Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Local vegetation near streams and rivers can be impacted when mine waste containing dissolved elements (e.g Cu, Zn, Pb, and As) enters water-bodies (Lewis, 1977;Gammon, 1970;Pagenkopf et al, 1974;Warnick & Bell, 1969). An influx of dissolved trace elements can affect organisms like insect larvae, bivalve mollusks, and microorganisms, which in turn affect larger organisms up the food chain (Wright & Zamuda, 1987;Qiu et al, 2007). As shown in literature (Krishnamurti et al, 2005;Reglero et al, 2008;Moreno-Jimenez et al, 2009), bioaccumulation in local vegetation will directly affect local fauna by the transfer of metals from one organism to another.…”
Section: Uptake and Effects On Faunamentioning
confidence: 96%